EFFECTIVENESS OF DEEP BREATHING EXERCISE AND INCENTIVE SPIROMETRY ON OXYGEN SATURATION AND PEAK EXPIRATORY FLOW RATE IN POSTEXTUBATION ICU PATIENTS: A QUASI-EXPERIMENTAL STUDY - Nugroho Ari Wibowo; Diah Priyantini; Gangga Kristin Nurfiyatul Jannah; Miranda Meifa (NurseLine Journal, 2025)
Background: Reintubation of patients in the ICU due to respiratory failure is a serious problem in medical world. Supportive therapy is needed for breathing exercises to prevent reintubation due to respiratory muscle weakness. Objective: Aims to analyze effectiveness of deep breathing exercise and Incentive spirometry on oxygen saturation and peak expiratory flow rate inextubated patients. Methods: A quantitative, quasi-experimental design with 33 respondents (11 in the deep breathing group, 11 in the incentive spirometry group, and 11 in the combined deep breathing and incentive spirometry group), recruited through purposive sampling. The independent variable was the combination of Deep Breathing and Incentive Spirometry, implemented according to the module guidelines. The dependent variables were oxygen saturation, measured by pulse oximetry, and peak expiratory flow rate, measured by a peak flow meter. Data were analyzed using a paired sample t-test. Results: Deep breathing exercises and incentive spirometry showed a significant effect on oxygen saturation, as shown in the combined results (p = 0.000; Delta = 4.55). Peak expiratory flow rate also showed significant deep breathing exercise and incentive spirometry interventions,with the most significance value in the combination intervention (p = 0.000; Delta = 130.27). Conclusion: The combination of deep breathing exercises and incentive spirometry interventions showed greater effectiveness, suggesting it may be a supportive intervention for post-extubation patients.